Experimental and numerical studies of AL7020 formability under orthogonal loading paths with considering yield surface distortion. (April 2017) - Yue, Z.M.; Badreddine, H.; Saanouni, K.; Perdahcioglu, E.S.
Abstract: In metal forming, material points are often subject to complex loading paths even if the applied loading imposed by the forming tools is simple monotonic loading paths. Including the yield surface distortion effect in constitutive equations is expected to highly enhance the capability of the model in simulating the material forming behavior under complex loading paths. In the present work, fully coupled anisotropic constitutive equations with mixed isotropic and kinematic nonlinear hardening strongly coupled with isotropic ductile damage are improved, considering the subsequent yield surfaces distortion. A model based on the framework of non-associative plasticity theory has been developed recently. In this model, a distortion stress tensor S ̲ d replaces the usual deviator stress tensor S ̲ in the yield criterion and dissipation potential. Three parameters X l 1 c, X l 1 p, and X l 2 are introduced in the coupled constitutive equations, to be used to control the subsequent yield surfaces distortion. This model is applied and compared with the experiments specifically performed for that purpose. Series of experiments are conducted using the material AL7020 to identify and validate the proposed model. Through the combined loading tests performed on Twente biaxial testing machine, the results of non-proportional loading paths demonstrate that the proposed model can fully represent the forming behavior when complex loading paths. The influence of the yield surface distortion on the plastic flow and on the ductile damage evolution is also discussed in this study. Graphical abstract: Highlights: A fully coupled anisotropic constitutive equations with mixed isotropic and kinematic nonlinear hardening fully coupled with isotropic ductile damage is improved, considering the subsequent yield surfaces distortion. Through replacing the usual deviator stress tensor "S" with "Sd ", the yield surface distortion is realized, and three parameters "Xl1c ", "Xl1p ", and "Xl2 " are introduced to control the subsequent yield surfaces distortion. Through the combined loading tests performed on Twente biaxial testing machine, the results of non-proportional loading paths validate the proposed model. The influence of the yield surface distortion on the plastic flow and on the ductile damage evolution is also discussed in this study.